RESTORASI MANAJEMEN WAKAF DARI TRADISIONAL MENUJU PROFESIONAL - Wawan Juandi; Nawawi Nawawi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2020)
This study found that waqf is a form of worship that contains a distinct benefit. The distinction of waqf is that its object is permanent and its benefits continue to flow for the benefit of Islamic preaching and the economic improvement. Waqf is not only in the form of immovable objects but also includes all handy objects. This is in accordance with the words of the Prophet, "hold on to the point and give the result." So far, waqf has only been managed traditionally. It needs restoration so that becomes professional, and becomes a potential and useful asset for the benefit of Muslims. Waqf in the history has contributed to Muslim civilization. Waqf as a medium for Islamic preaching (dakwah), such as mosques, universities, and schools because it will becomes the glory of Islam as rahmatal lil 'alamin. Waqf also has a function as a medium for improving the economy of Muslims, because a very urgent need is property to meet the needs of life. Meanwhile, what people face today is poverty. One of them is waqf which is managed productively and professionally. Fourteen centuries ago, the Prophet said, "almost poverty has fallen into disbelief". Therefore, it is necessary to change the mindset or rejuvenate that Islam is not synonymous with poverty and backwardness. So, it is inappropriate for Muslims to live in an Islamic country in poverty even if they are kafir dzimmi (kafir who has the protection in Islamic country).